Declining newborn intramuscular vitamin K prophylaxis predicts subsequent immunisation refusal: A retrospective cohort study. (14th April 2015) - Bernhardt, Helen; Barker, David; Reith, David M; Broadbent, Roland S; Jackson, Pamela M; Wheeler, Benjamin J
<x xml:space="preserve">Abstract</x> Aim Low rates of childhood immunisation are linked to outbreaks of infectious disease. Identifying and addressing barriers to immunisation may lead to improved immunisation rates. Immunisation and newborn vitamin K prophylaxis have many similarities. We aimed to investigate whether parents who decline newborn vitamin K are also more likely to decline subsequent childhood immunisations. Methods We undertook a retrospective cohort study, examining the relationship between vitamin K administration and immunisation uptake by parents of babies born over a 2‐year period (January 2010–December 2011) in Dunedin, New Zealand (NZ). Both written and electronic data from a single birthing unit and the NZ National Immunisation Register (NIR) were analysed to ascertain the relationship between declining newborn vitamin K prophylaxis and subsequent immunisation uptake. Results Records for 3575 babies were examined. Ninety‐two per cent of infants received intramuscular, and 5% received oral vitamin K. An increased risk ratio for non‐immunisation of 14.1 (95% confidence interval 7.8–25.9) for babies whose parents declined vitamin K was identified. Receiving oral vitamin K was also associated with subsequent non‐immunisation, with a risk ratio of 3.5 (95% confidence interval 1.7–7.3). Conclusions Parents who decline newborn vitamin K are more likely to decline immunisation for their child. These parents, as well as those that elect for oral vitamin K, are a small but easily identifiable group to whom additional education about the benefits of immunisation could be offered. This is especially pertinent at a time when there is a resurgence of immunisation preventable diseases.